Serum-Free Xenogen-Free Culture Conditions Support Human Explant-Derived Cardiac Stem Cell Growth - Mount, Seth (Université d'Ottawa / University of Ottawa, 2017)
Autologous explant-derived cardiac stem cell (EDC) therapies are a promising therapy for ischemic cardiomyopathy, but straightforward clinical translation is limited by traditional culture conditions which are often supplemented with ill-defined and xenobiotic components such as fetal bovine serum. Therefore, we investigated the influence of a commercially sourced serum-free (SF) xenogen-free medium on human EDC yield, phenotype, in vitro measures of EDC performance, and post-infarct cardiac repair using an immunodeficient mouse model of acute myocardial infarction. Despite reduced production of several pro-cardiogenic cytokines, SF EDCs promoted similar vessel formation, circulating stem cell recruitment and cardiogenic differentiation as compared to standard cultures. Transplant of SF EDCs into immunodeficient mice 1 week after myocardial infarction boosted post-ischemic repair beyond that of standard EDCs by enhancing viable myocardium within the infarct. These findings demonstrate that serum-free culture methods provide a superior cardiac-derived cell product with ready clinical translatability.